Vanaraja and Srinidhi poultry Bridging the gap of chicken meat and egg in north east hill region of India - Singh, Mahak; Kalita, H; Mishra, V K (Indian Farming, 2024)
North-East India is a live museum of anthropology and one of the biodiversity hotspot. The food habits of the people in the North-East India are mainly non-vegetarian. The per capita consumption of animal source food is highest in the region (51 kg per capita in Nagaland) on national level. The tribal people mainly prefer pork followed by chicken meat. In poultry, meat of indigenous or local ordesi birds are highly preferred because of texture and flavour. However, productivity of local bird is very low and unable to fulfill the current demand. Therefore, ICAR has introduced improved rural germplasm like Vanaraja and Srinidhi through Poultry Seed Project. In NEH region, there are four ICAR-Poultry Seed Projects catering to the demand of tribal farmers. With these efforts, Vanaraja and Srinidhi birds are household name in the remotest corner of the region. Their hardiness ensures these birds to survive from sub-tropical to temperate climate. This has ensured food and economical security of the resource poor farmers in NEH region and bridged the gap of chicken meat and egg.